Sentimen Politik dan Volatilitas Pasar: Reaksi Indeks Pefindo 25 terhadap Pemilu Presiden 2024 - Hendi Wijaya; Tarisa Nur Asyifa; Kania Aini Salmabila; Tasya Bella Oktaviani; Dinan Maolana Ibrahim; Okta Eka Putra (Rashid : Journal of Economic, 2025)
This study aims to determine whether or not there are changes in stock returns and trading volume before and after the election. This study uses a quantitative method with an event study approach to analyze market reactions to the 2024 Presidential Election. The results of the study showed that there was no significant difference in stock returns and trading volume of the Pefindo 25 Index. This finding indicates that investors consider fundamental factors more than short-term political sentiment. This study concludes that the 2024 Presidential Election does not have a significant impact on stock returns and trading volume of the Pefindo 25 Index. Market stability indicates that investors have anticipated this political event in advance. This finding confirms the importance of fundamental factors in investment decision making compared to short-term political sentiment.